Analisis Readiness Parts di Era Volatility, Uncertainty, Complexity & Ambiguity (VUCA) Supply Chain Melalui Claim Warranty Spareparts Menggunakan Metode Quality Control Circle studi kasus Industri Pertambangan PT Pamapersada Nusantara - Wijanarto, Aris; HM, Gatot Basuki (Jurnal SENOPATI : Sustainability, Ergonomics, Optimization, and Application of Industrial Engineering, 2025)
The achievement of spare parts readiness has decreased in the VUCA Supply Chain era of PT Pamapersada Nusantara. Spare parts readiness is an important factor for the Supply Chain department at PT Pamapersada Nusantara because it is the key to the continuity of a maintenance activity so that mining activities run smoothly, so the purpose of this study is to be able to provide spare parts in the VUCA Supply Chain era through Claim Warranty using the PDCA (Plan, Do, Check, Action) method. The results and discussion were obtained six root causes of the problem, then PDCA and Min-Max analysis was carried out as a method of controlling the readiness level. The stock level condition is applied with a Min of 3 and a Max of 5 to maintain a readiness level that is always available.